Extreme scattering events towards two young pulsars. Issue 4 (1st December 2017) - Kerr, M; Coles, W A; Ward, C A; Johnston, S; Tuntsov, A V; Shannon, R M
Abstract: We have measured the scintillation properties of 151 young, energetic pulsars with the Parkes radio telescope and have identified two extreme scattering events (ESEs). Towards PSR J1057−5226, we discovered a 3 yr span of strengthened scattering during which the variability in flux density and the scintillation bandwidth decreased markedly. The transverse size of the scattering region is ∼23 au, and strong flux density enhancement before and after the ESE may arise from refractive focusing. Long observations reveal scintillation arcs characteristic of interference between rays scattered at large angles, and the clearest arcs appear during the ESE. The arcs suggest scattering by a screen 100–200 pc from the Earth, perhaps ionized filamentary structure associated with the boundary of the local bubble(s). Towards PSR J1740−3015, we observed a 'double dip' in the measured flux density similar to ESEs observed towards compact extragalactic radio sources. The observed shape is consistent with that produced by a many-au scale diverging plasma lens with electron density ∼500 cm −3 . The continuing ESE is at least 1500 d long, making it the longest detected event to date. These detections, with materially different observational signatures, indicate that well-calibrated pulsar monitoring is a keen tool for ESE detection and interstellar medium (ISM) diagnostics. They illustrate the strong role au-scale non-Kolmogorov density fluctuations and the local ISM structure play in such events and are key to understanding both their intrinsic physics and their impact on other phenomena, particularly fast radio bursts.